Isolation, Production and Characterisation of Novel Gelatinase Enzyme From Bacillus Spp - Joseph, Jini; Sasidharan, Harsha; O.S, Chithira (International Journal of Scientific Research in Biological Sciences, 2018)
Nowadays gelatinase have received considerable attention as targets for drug development because of their potential role in connective tissue degradation associated with tumor metastasis. The potential uses of Gelatinase and their high demand, necessitates the need for the discovery of new strains of bacteria that produce enzymes with novel properties and with low cost industrial medium. The present study was conducted to isolate and identify gelatinase producing microorganisms as well as optimize the medium and cultural conditions for maximum enzyme production. Isolates obtained from fish processing wastes were examined for gelatinase production.The medium parameters were optimized for maximum production of gelatinase enzyme by the efficient isolate.Optimizing its abiotic factors, maximum enzyme activity was achieved at 48h incubation period, pH 7, 40°C temperature, lactose as carbon source and a gelatin concentration of 0.2%. The identity of the strain was confirmed by PCR reaction with universal primers (27F and 1492 R), sequencing and then by the BLAST analysis. The results showed that the isolated bacteria had highest homology (100%) with Bacillus thuringiensis strain O3.The enzyme produced under all the optimum was then purified by ammonium sulphate precipitation (40%) and dialysis. The final purification after dialysis yielded specific activity of 45.85 IU/ml. The purity of enzyme preparation was assessed by SDS PAGE Gel electrophoresis and was found to be a single band with a molecular weight of approximately 66 kDa.The study could isolate and identify a potent gelatinase producing Bacillus strain that can be used for the development of gelatinase enzyme production.